Albanian higher education reform: An institutional document analysis - Vucaj , Indrit (Journal of Interdisciplinary Studies in Education, 2017)
This qualitative research synthesis paper employs an institutional document analysis methodology in place, time and context to crystallize and discover text meaning of the recent higher education reform in Albania. Feedback theory systems, educational institutions theory, institutional change theory, student integration model theory and rational choice theory are the integrated lenses in interpreting and conveying various contingencies and other contextual factors related to Albanian higher education reform. The synthesis found merit in addressing past and present climate in higher education, increased enrollment rates without infrastructure, abuse of educational system, lack of educational institutional autonomy, need to develop higher education institutions with different statuses, low purchasing power of Albanian students and lack of collaborative opportunities which were previously reported to constitute a need for a governmental reform.